Evaluation of self-etching primer on bond strength in feldspathic ceramic (Research, Society and Development, 2021)
The aim of the study was to evaluate the effect of self-etching silane primer on long-term bonding strength on feldspathic ceramic. Ceramic blocks (IPS Empress CAD, Ivoclar Vivadent) were cut with a low-speed diamond disk (Isomet 1000, Buehler) into 40 blocks of 12x7x6mm, under water cooling, and randomly divided into two groups (n=20), according to the surface conditioning: hydrofluoric acid (HF) (Condac, FGM) or self-etching silane primer (MEP) (Monobond Etch and Prime, Ivoclar Vivadent). After the blocks were bonded to composite resin blocks (12 x 7 x 3mm) (Liss, FGM) with a light cured cement (Variolink Esthetic LC, Ivoclar Vivadent) and LED photoactivation (Radii Cal, SDI) for 40 s on each luting interface line. The sets were cut in sticks with 1-mm2 cross-section composed of ceramic/cement/composite and tested after 24h (baseline) and 90 days aging by stored in distilled water at 37ºC. Microtensile bond strength testing (mTBS) was performed using a universal machine (DL-1000, EMIC) submitted to traction with speed of 0.5mm/ min until rupture of adhesion. Fracture of specimens were examined under stereomicroscopy to determine the failure pattern. Bond strength (MPa) was calculated, and the failure pattern and interface topography were assessed using scanning electron microscopy (SEM). No significant different mTBS was observed between groups HF and MEP (p>0.05). Storage time of the samples did not affect the mTBS from the groups.  Surface etching pattern with HF produced higher surface alterations than a self-etching primer. Application of MEP may be considered an alternative for silanization for feldspathic ceramic.